1998
DOI: 10.1044/jslhr.4102.232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Vocal Performance of Children Using a Voice Range Profile Index

Abstract: Voice range profiles (VRPs) were analyzed according to 11 frequency, intensity, and morphological characteristics for 94 normal children and 136 children with vocal fold pathologies (ages 6-11 years). Normative data are presented showing marked differences between the groups. Using a specific combination of the child's age, the highest vocal fundamental frequency, the lowest intensity, and the slope of the upper VRP contour, a Voice Range Profile Index for Children (VRPIc) may be constructed using discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 8 publications
0
40
1
13
Order By: Relevance
“…Frequency and intensity range were measured using the Voice Range Profile function of the Computerized Speech Lab (Kay Elemetrics, Lincoln Park, NJ, USA, 1992). The procedure developed by Heylen et al [29] was used. A unidirectional dynamic Shure SM-48 microphone located at a distance of 15 cm from the mouth and angled at 45° was used.…”
Section: Methodsmentioning
confidence: 99%
“…Frequency and intensity range were measured using the Voice Range Profile function of the Computerized Speech Lab (Kay Elemetrics, Lincoln Park, NJ, USA, 1992). The procedure developed by Heylen et al [29] was used. A unidirectional dynamic Shure SM-48 microphone located at a distance of 15 cm from the mouth and angled at 45° was used.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, multidimensional indices have already suggested their benefit in clinical practice (the body mass index [weight (kg)/height 2 (m 2 )] is a good illustration of the efficacy of combining variables). In voice research, multivariate techniques have also proved their usefulness, as shown by the Dysphonia Severity Index [13] and the Voice Range Profile Index for Children [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Weighted sums are commonly used in multivariate statistical methods such as logistic regression or discriminant analysis. Multivariate techniques also prove to be useful in voice research as shown by the dysphonia severity index (DSI) [5] and the voice range profile index for children (VRPIc) [6] . Both indexes are able to assess the degree of vocal pathology for individual subjects.…”
Section: Introductionmentioning
confidence: 99%